An investigation into male infertility caused by hormonal imbalance and hypertension brought on by SARS-CoV-2 - Parameswari R; Kasthuri K; Babujanarthanam R; Ganesamoorthy R; Gomathi R; Yogesh T (Middle East Fertility Society Journal)
Abstract Background Recent statistics suggest that birth rates are declining worldwide; in parallel, recent studies have also shown that birth rates have decreased since the emergence of SARS-CoV-2. The etiology of the viral infection and its relationship to fertility is currently being investigated. Aim As a result, this study focused on males who recovered from SARS-CoV-2 and had hormonal anomalies associated with high blood pressure, which might lead to male infertility. Methods The study population consisted of men aged 20–39 years (N = 150) from the Vellore region who had recovered from SARS-CoV-2 infection within the previous 6 months, as determined through a questionnaire-based survey. Ethical approval was obtained from the relevant institutional review board prior to data collection. Semen samples were collected and analysed according to the World Health Organization (WHO) guidelines (2021) for conventional semen parameters. Standard hormonal and biochemical tests were performed using established protocols. In addition, trace element concentrations in serum and seminal plasma were analysed. Hypo-osmotic swelling test (HOST) was used to assess sperm viability, and acrosome integrity was evaluated with staining techniques. Results Increased blood pressure (BP) was suggested by semen parameters with reduced sperm motility and sperm count in patients infected with SARS-CoV-2 compared to healthy subjects. Despite the reduction in sperm protein, it was associated with a decrease in biochemical nutrients. Furthermore, poorer antioxidant and biochemical markers against ROS were observed, and these differences were statistically significant (P < 0.05). Differences were identified between SARS-CoV-2 recovered men and healthy fertile men in terms of sperm protein fragmentation and loss of sperm membrane integrity, accompanied by structural damage to the acrosome. Conclusion This study confirmed that SARS-CoV-2 enters the body via angiotensin-converting enzyme 2 (ACE2) in recovered patients, affecting the physiological homeostasis mechanism by triggering blood pressure changes associated with declined male reproductive characteristics (especially testosterone), resulting in a poor semen profile and infertility.